Hubungan Tingkat Pengetahuan tentang Malaria dengan Pemakaian Kelambu pada Kapal Penumpang yang berasal dari daerah Endemis Malaria di Kutai timur - Heny Surya Widiyaningsih; Irfansyah Baharuddin Pakki; Ratih Wirapuspita Wisnuwardani (J-KESMAS: Jurnal Kesehatan Masyarakat, 2025)
Malaria is an important tropical parasitic disease in the world, and remains a major health problem. An estimated 41% of the world's population lives in areas at high risk of malaria infection, especially in tropical and subtropical countries. Malaria vector control is one of the efforts to prevent and control malaria which aims to break the chain of malaria transmission. This study aims to analyze the relationship between the level of knowledge about malaria with the use of mosquito nets on passenger ships at Samarinda port. The method used was quantitative with a cross sectional design involving 62 respondents selected by simple random sampling. The results of the study obtained a p-value of 0.701 with the conclusion that there is no relationship between the level of knowledge about malaria with the practice of using mosquito nets.Based on this study, it is hoped that there will be education on the importance of wearing mosquito nets as an effort to prevent malaria.